The effectiveness of participatory electronic games in developing the skill of numerical sense for a mathematics course for elementary school students - Al-Kathiri, Mai Bandar Naif (Journal of Educational and Psychological Sciences, 2021)
The study aimed to determine the numerical sense skills that can be developed using participatory electronic games for fourth-grade students, used the semi-experimental approach, and the study sample consisted of (40) female students The fourth elementary school was divided into two groups, an experimental group of 20 students, who studied the skill of numerical sense through participatory electronic learning games, and a group of 20 students who studied the skill of numerical sense in the traditional learning method; Where the two groups applied to the pre / post achievement test, and the study found that the experimental group students exceeded the control group in the post test. The higher levels of the experimental group students in the post-test than their degrees in the pre-test in the achievement test, and thus the study for the effectiveness of the electronic study Participatory skill development in the numerical sense of mathematics course for female students of experimental group compared to female students of control group.
Keywords: motivation; fourth grade; pre-test; post-test